THE APPLICATION OF COVARIANCE BASED STRUCTURAL EQUATION MODELING ON SECONDARY DATA OF ACCREDITED SCHOOL IN MAKASSAR - USMAN (90115011), FAHRUL
The national standar of education is a minimal criteria in the implementation of the educational system that must be met in the educational unit. School accreditation is a series manifestation of national education standard. There are 8 national education standards, Graduate Competence Standar, Content Standard, Education Process Standard, Teaching Staff Standard, Standard of Facility and Infrastructure, Management Standard, Financial Education Standard, and Education Assesment Standard. This research was meant to investigate the influence of three national education standards, those are graduate competence, education and the staff, and education facility, more specifically on how schools in Makassar acquired school accreditation model by using structural equation modeling. The application SEM of this model used covariance based. The first stage was to input school accreditation data, next was determining the step based on existing theory, the last was to estimate model parameter measurement and structural model by using maximum likelihood (MLE), afterwards, the model used was then evaluated and if the model works then the next steps are interpretation and extrapolation. However, if the criteria are not met in accordance to goodness of fit (GOF), then the modification should be in place to get a proper and workable model. The date used was secondary data with 40% from national education standard. Descriptive analysis was imposed upon two type of school including public and private senior high schools. Public school with A accredited and private with B accredited. If the result achieved based on the distance of district official could affect the accreditation of school, but that is not happened. Based on SEM analysis, facility could positively the school accreditation. Although based on the model goodness test it was found that there were less fit models, but the CFI and TLI models were close to 0.90 so it was acceptable and the model was considered feasible